Control of a simple morphing mechanism for UAVs - Muhammad Farid As'ad (2015)
Morphing wings on aircrafts is a subject of intense research due to its promise of enabling greater maneuverability, improved fuel efficiency and enhanced performance. This project focuses on the development criteria of a morphing wing unmanned aerial vehicle (UAV) such as morphing method, materials and effectiveness of using a morphing wing on a UAV as compared to the conventional control methods. Also, the report will explore the feasibility of utilizing Shape Memory Alloy (SMA) as means of actuating the morphing of the wing structures. The SMA being used in this report is trained to have a two-way memory effect that would enable it to actuate the wing flaps of the UAV. The SMA is trained and actuated by means of electricity. With research from previous studies of deflection rates and deflection times, the feasibility of using NiTi as wing morphing actuation will be analyzed. From his research on this topic, the author has finds that despite its several advantages, the poor recovery length/strain of the NiTi deems a simple mechanism using the material for morphing wing actuation not suitable. Even at this present moment, electronic servos are still the better choice for UAVs due to its relatively light weight and high strength. The findings from the research are to serve as a guideline for future development of SMA usage in wing morphing actuation. The performance and capability of SMA actuators can be better gauged through understanding the above results and therefore open up more opportunities to further improve on future design studies of such nature.